Media Digital Pemasaran Perbankan Syariah - Irmayana (Danudirja Setyabudi Nusantara, 2025)
This study examines digital media in Islamic banking marketing. The type of research conducted is library research with a qualitative descriptive approach. The study results indicate that Islamic banks in Indonesia have transformed digitally by optimising various digital platforms such as Facebook, Twitter (X), Instagram, and official websites to reach customers more widely, quickly, and efficiently. For instance, they use Facebook to conduct live Q&A sessions, Twitter for customer service, Instagram for product showcases, and official websites for online banking services. Each medium has its characteristics and advantages that are used to introduce products, build a positive image, and strengthen interactive relationships with customers. The main characteristics of Islamic marketing, which include theistic (Rabbâniyyah), ethical (Akhlâqiyyah), realistic (Al-Wâqi’iyyah), and humanistic (al-Insâniyyah) values, show that marketing is not only oriented towards profit, but also towards the common good, balance, and human dignity.